Technical Efficiency of Thai Manufacturing SMEs: A Stochastic Frontier Analysis - Teerawat Charoenrat; Charles Harvie (Australasian Accounting, Business and Finance Journal, 2013)
A major motivation of this study is to examine the factors that are the most important in contributing to the relatively poor efficiency performance of Thai manufacturing small and medium sized enterprises (SMEs). The results obtained will be significant in devising effective policies aimed at tackling this poor performance. This paper uses data on manufacturing SMEs in the North-eastern region of Thailand in 2007 as a case study, by applying a stochastic frontier analysis (SFA) and a technical inefficiency effects model. The empirical results obtained indicate that the mean technical efficiency of all categories of manufacturing SMEs in the North-eastern region is 43%, implying that manufacturing SMEs have high levels of technical inefficiency in their production processes. Manufacturing SMEs in the North-eastern region are particularly labour-intensive. The empirical results of the technical inefficiency effects model suggest that skilled labour, the municipal area and ownership characteristics are important firm-specific factors affecting technical efficiency. The paper argues that the government should play a more substantial role in developing manufacturing SMEs in the North-eastern provinces through: providing training programs for employees and employers; encouraging a greater usage of capital and technology in the production process of SMEs; enhancing the efficiency of state-owned enterprises; encouraging a wide range of ownership forms; and improving information and communications infrastructure.
Keywords: Technical efficiency; Stochastic frontier analysis (SFA); Small and medium sized enterprises (SMEs); Manufacturing; North-eastern region of Thailand